2011
DOI: 10.1002/ijc.25544
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of hnRNP G and hTra2‐beta1 correlate with opposite outcomes in endometrial cancer biology

Abstract: HnRNP G is a member of heterogeneous nuclear ribonucleoprotein (hnRNP) family with potent tumor suppressive activities. Human transformer-2-beta1 (hTra2-beta1) belongs to the arginine-serine rich like proteins and is found over-expressed in various human cancers. It was recently shown that hnRNP G and hTra2-beta1 exert antagonistic effects on alternative splicing. In our study we explored the impact of these two factors in tumor biology of endometrial cancer (EC). EC tissues (n 5 139) were tested for hnRNP G a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…SMARCC1 protein upregulation has been reported in prostate cancer [62], colorectal cancer [63] and cervical intraepithelial neoplasia [62]. TRA2B over-expression was observed in endometrial cancers [64], Gastric cancer cells [65] and cervical cancer [66]. In addition, elevated levels of CBX3 expression in tumor stem cell (TSC)-enriched osteosarcoma cultures was detected [67].…”
Section: Discussionmentioning
confidence: 98%
“…SMARCC1 protein upregulation has been reported in prostate cancer [62], colorectal cancer [63] and cervical intraepithelial neoplasia [62]. TRA2B over-expression was observed in endometrial cancers [64], Gastric cancer cells [65] and cervical cancer [66]. In addition, elevated levels of CBX3 expression in tumor stem cell (TSC)-enriched osteosarcoma cultures was detected [67].…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, hnRNP G and Tra2-β1 could also antagonize the binding of each other to RNA (20) (Figure 7A). This later mode of action would explain the opposite effects observed for these two proteins on endometrial cancer progression (59). As illustrated in Figure 4C, we also observed a competition between these two proteins when both Tra2-β1 and hnRNP G RRMs are bound to the SMN2 derived 5′-UCAAAAAGAAG-3′ RNA.…”
Section: Discussionmentioning
confidence: 99%
“…RBMX gene, also known as HnRNP G , is a member of heterogeneous nuclear ribonucleoprotein (hnRNP) family and can collaborate with hTra2 - beta1 (human transformer-2-beta1) as sequence-specific transacting factors to exert antagonistic effects on alternative splicing which is recognized as a pivotal mechanism in regulation of gene expression and associated to tumorigenesis and metastasis of a wide variety of human cancers [ 26 ]. It is proposed that the ratio of hnRNP G/hTra2-beta1 influenced cellular splicing preference [ 27 , 28 ]. Some researches revealed that hnRNP G-protein showed as tumor suppressor in endometrial carcinoma [ 27 ] and oral squamous cancer [ 29 ], its activity was elicited by transactivating tumor suppressor Txnip gene [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that the ratio of hnRNP G/hTra2-beta1 influenced cellular splicing preference [ 27 , 28 ]. Some researches revealed that hnRNP G-protein showed as tumor suppressor in endometrial carcinoma [ 27 ] and oral squamous cancer [ 29 ], its activity was elicited by transactivating tumor suppressor Txnip gene [ 30 ]. A recent research showed that high frequency of hnRNP G-protein reduction and loss of expression in precancerous and human oral squamous cell carcinoma tissue specimens, suggesting that reduction in hnRNP G may play an important role in the early pathogenesis of oral squamous cell carcinomas [ 31 ].…”
Section: Discussionmentioning
confidence: 99%